Analisis Implementasi Kebijakan Standar Pelayanan Minimal Bidang Kesehatan (SPM-BK) Orang Terduga Tuberkulosis di Kabupaten Pesawaran Provinsi Lampung - Rizka Dwiyovita; Martha Irene Kartasurya; Nurjazuli Nurjazuli (Universitas Malahayati Lampung, 2023)
ABSTRACT The minimum service standard is a benchmark for the type and quality of services provided to the community at a minimum. The coverage of TB suspects receiving services in Pesawaran District has not reached the national target (100%). To analyze the implementation of minimum service standard policies in the health sector for people suspected of having TB. This research is a qualitative research with a case study approach. The research locations were carried out at the Pesawaran District Health Office, Kedondong Health Center, Kota Dalam Health Center, Kalirejo Health Center, and Roworejo Health Center. Primary data was obtained from in-depth interviews and observations, secondary data was obtained from document review. There were 11 informants in this study consisting of 3 main informants and 9 triangulation informants. The implementation of the policy on minimum service standards in the health sector for people suspected of having TB has not run optimally. There are variables that are not maximized so that they hinder policy implementation, namely resources, communication between organizations and implementing activities, characteristics of implementing agencies, dispositions of implementing agencies, and environmental, social and economic conditions. Implementation of minimum service standard policies in the health sector for people suspected of having TB can be carried out optimally by increasing cooperation and coordination in both government and private circles. Keywords: Qualitative, Minimum Service Standards, Tuberculosis ABSTRAK Standar pelayanan minimal merupakan tolak ukur jenis dan mutu pelayanan yang diberikan kepada masyarakat secara minimal. Cakupan terduga TB yang mendapatkan pelayanan Kabupaten Pesawaran belum mencapai target nasional (100%). Untuk menganalisis implementasi kebijakan standar pelayanan minimal bidang kesehatan (SPM-BK) orang terduga TB. Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi kasus (case study). Lokasi penelitian dilakukan di Dinas Kesehatan Kabupaten Pesawaran, Puskesmas Kedondong, Puskesmas Kota Dalam, Puskesmas Kalirejo, dan Puskesmas Roworejo. Data primer diperoleh dari hasil wawancara mendalam dan observasi, data sekunder diperoleh dari telaah dokumen. Informan penelitian ini berjumlah 11 orang yang terdiri dari 3 informan utama dan 9 informan triangulasi. Implementasi kebijakan SPM-BK orang terduga TB belum berjalan maksimal. Terdapat variabel yang belum maksimal sehingga menghambat implementasi kebijakan, yaitu sumber daya, komunikasi antar organisasi dan kegiatan pelaksana, karakteristik badan pelaksana, disposisi pelaksana, serta kondisi lingkungan, sosial, dan ekonomi. Implementasi kebijakan SPM-BK orang terduga TB dapat dilakukan secara optimal dengan meningkatkan kerjasama dan koordinasi baik dilingkungan pemerintah maupun swasta. Kata Kunci: Kualitatif, Standar Pelayanan Minimal, Tuberkulosis.